Monumental misjudgements? Early conservative interventions and their impact on Orcadian Neolithic sites - Ritchie, Georgina (The University of Edinburgh, 2014)
The contemporary experience of visiting many Neolithic sites in Orkney is dominated by the physical manifestations of early conservative interventions; the most striking of these being a series of cover-houses, installed over chambered tombs to ensure their protection from the elements. These shelters range in scale from small concrete domes enclosing the interior of the monuments (such as that over the Knowe of Yarso, depicted in the cover image), to a vast free-standing steel enclosure (see Figure A1 below). Yet despite their dominant forms, these constructions remain curiously little discussed in academia, and specialist sources must be consulted to establish even a date of installation. The current work therefore aims to illuminate these ventures, and to examine the wider suite of consolidation works involved in their installation, plus the motivations and historical context by which they were stimulated. The impact of these interventions will then be considered by examining their effect upon i) the archaeology as a scientific resource, ii) the current condition of the sites, and iii) the contemporary experience of their visitation.
Keywords: Neolithic heritage; Scottish architecture; architectural conservation